2017
DOI: 10.1080/10705511.2017.1312407
|View full text |Cite
|
Sign up to set email alerts
|

Power in Bayesian Mediation Analysis for Small Sample Research

Abstract: It was suggested that Bayesian methods have potential for increasing power in mediation analysis (Koopman, Howe, Hollenbeck, & Sin, 2015; Yuan & MacKinnon, 2009). This paper compares the power of Bayesian credibility intervals for the mediated effect to the power of normal theory, distribution of the product, percentile, and bias-corrected bootstrap confidence intervals at N≤ 200. Bayesian methods with diffuse priors have power comparable to the distribution of the product and bootstrap methods, and Bayesian m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 43 publications
4
77
0
1
Order By: Relevance
“…Although one of these 14 studies reported that both frequentist and BayesN methods lead to minimal bias in the parameter estimates (Yuan & MacKinnon, 2009), 6 of 14 studies reported that both methods resulted in poor parameter estimates (Browne & Draper, 2000, 2006Depaoli, 2013; 2 simulation studies in McNeish, 2016a;van de Schoot et al, 2015). The remaining studies show that the conclusion depends on: the choice of the naive prior distribution (McNeish, 2016b;McNeish & Stapleton, 2016;e.g., McNeish and Stapleton (2016) show that BayesN with Inverse Gamma or half-Cauchy prior distributions for the variance components in a multilevel model perform better in comparison to the other BayesN option with a uniform prior distribution); the choice of the frequentist estimation method to which the BayesN is compared (Koopman, Howe, Hollenbeck, & Sin, 2015;McNeish, 2016b;Miočević et al, 2017;e.g., McNeish (2016b) concludes that REML with Kenward-Roger correction performs better than ML and BayesN); or that the conclusions depend on the interest in either point estimates or interval estimates (2 simulation studies in Chen, Choi, Weiss, & Stapleton, 2014).…”
Section: Bayesn Vs Frequentist Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although one of these 14 studies reported that both frequentist and BayesN methods lead to minimal bias in the parameter estimates (Yuan & MacKinnon, 2009), 6 of 14 studies reported that both methods resulted in poor parameter estimates (Browne & Draper, 2000, 2006Depaoli, 2013; 2 simulation studies in McNeish, 2016a;van de Schoot et al, 2015). The remaining studies show that the conclusion depends on: the choice of the naive prior distribution (McNeish, 2016b;McNeish & Stapleton, 2016;e.g., McNeish and Stapleton (2016) show that BayesN with Inverse Gamma or half-Cauchy prior distributions for the variance components in a multilevel model perform better in comparison to the other BayesN option with a uniform prior distribution); the choice of the frequentist estimation method to which the BayesN is compared (Koopman, Howe, Hollenbeck, & Sin, 2015;McNeish, 2016b;Miočević et al, 2017;e.g., McNeish (2016b) concludes that REML with Kenward-Roger correction performs better than ML and BayesN); or that the conclusions depend on the interest in either point estimates or interval estimates (2 simulation studies in Chen, Choi, Weiss, & Stapleton, 2014).…”
Section: Bayesn Vs Frequentist Methodsmentioning
confidence: 99%
“…In 7 out of 22 studies that examined BayesN and frequentist methods, no severely biased estimates were reported when using BayesN. However, 6 of these studies focused on mediation or multilevel mediation models and did not evaluate the variance parameters (2 simulation studies in Chen et al, 2014;Hox et al, 2014;Koopman et al, 2015;Miočević et al, 2017;Yuan & MacKinnon, 2009). As shown in Figure 5, the variance parameters are more often problematic in terms of bias than the structural parameters.…”
Section: Bayesn Vs Frequentist Methodsmentioning
confidence: 99%
See 3 more Smart Citations